2012
DOI: 10.1242/dev.072272
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of Rest leads to in vitro-specific derepression of neuronal genes during neurogenesis

Abstract: SUMMARYRest (RE1-silencing transcription factor, also called Nrsf) is involved in the maintenance of the undifferentiated state of neuronal stem/progenitor cells in vitro by preventing precocious expression of neuronal genes. However, the function of Rest during neurogenesis in vivo remains to be elucidated because of the early embryonic lethal phenotype of conventional Rest knockout mice. In the present study, we have generated Rest conditional knockout mice, which allow the effect of genetic ablation of Rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(94 citation statements)
references
References 42 publications
8
82
0
Order By: Relevance
“…While this manuscript was in preparation, a report was published showing that a neural-specific conditional Rest knockout does not alter neurogenesis, although effects were noted in cultured cells isolated from mouse (Aoki et al, 2012). Although further analysis of rest conditional knockouts is required, these findings support our conclusion that Rest is not essential for neurogenesis and highlight similarities between Rest function in zebrafish and mice.…”
Section: Figuresupporting
confidence: 71%
“…While this manuscript was in preparation, a report was published showing that a neural-specific conditional Rest knockout does not alter neurogenesis, although effects were noted in cultured cells isolated from mouse (Aoki et al, 2012). Although further analysis of rest conditional knockouts is required, these findings support our conclusion that Rest is not essential for neurogenesis and highlight similarities between Rest function in zebrafish and mice.…”
Section: Figuresupporting
confidence: 71%
“…In the nucleus of embryonic and neural stem cells, the REST-CoREST complex is thought to restrict the precocious expression of genes that promote differentiation as well as assist in lineage differentiation. In particular, in embryonic and neural stem cells, as well as in nonneural cells that have already differentiated, REST-CoREST appears to be crucial to suppressing the neural gene program (Abrajano et al, 2009a;Aoki et al, 2012;Chen et al, 1998;Gao et al, 2011;Jørgensen et al, 2009b;Sun et al, 2005). Less is known about the upstream mechanisms regulating REST-CoREST itself.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing controversies in the literature, principally with respect to the role of REST in maintaining ESC pluripotency (Buckley et al, 2009;Jørgensen et al, 2009a;Jørgensen and Fisher, 2010;Singh et al, 2008;Yamada et al, 2010), REST has been proposed to modulate the balance of stemness versus differentiation and lineage specification of both embryonic and neural stem cells (Aoki et al, 2012;Gao et al, 2011;Su et al, 2004;Sun et al, 2005). These activities involve the direct repression (or in some cases activation) of differentiation-promoting genes, especially of the neural lineage.…”
Section: P120-catenin In Modulating Stemness and Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The forkhead domain transcription factor FoxO3 is expressed in Sox2 + NSCs, and the absence of FoxO3 leads to a failure of NSCs to return to the quiescent state, ultimately leading to the depletion of the NSC pool (Renault et al 2009). In addition, the RE1 silencing transcription factor (REST), also known as NRSF, functions to repress the neuronal differentiation program in embryonic stem (ES) cells and early embryonic development (Yamada et al 2010;Mandel et al 2011;Aoki et al 2012;Soldati et al 2012). Recent work from my laboratory found that REST is expressed in type 1 cells, but is down-regulated in a subset of Ascl1 + cells and the majority of NeuroD1 + cells (Gao et al 2011).…”
Section: Maintenance and Cell Fate Specification Of Sgz Nscsmentioning
confidence: 99%